Phytoestrogen Bakuchiol Exhibits In Vitro and In Vivo Anti-breast Cancer Effects by Inducing S Phase Arrest and Apoptosis - Li, Li; Chen, Xueping; Liu, Chi C.; Lee, Lai S.; Man, Cornelia; Cheng, Shuk H. (Frontiers in Pharmacology, 2016)
Phytoestrogen has been proposed as an alternative to hormone replacement therapy, which has been demonstrated to promote a high risk of breast cancer. However, the effect of phytoestrogen on breast cancer development has not been fully understood. Bakuchiol is an active ingredient of a traditional Chinese herbal medicine Fructus Psoraleae, the dried ripe fruit of Psoralea corylifolia L. (Fabaceae). The in vitro and in vivo estrogenic activities and anti-breast cancer effects of bakuchiol have not been well studied. We found that bakuchiol induced the GFP expression in transgenic medaka (Oryzias melastigma, Tg, Chg:GFP) dose-dependently (0-1 µg/ml), demonstrating its in vivo estrogenic activity. Low dose of bakuchiol (1 µg/ml) induced the cell proliferation and ERα expression in MCF-7 cells, which could be blocked by the antiestrogen ICI 182780, suggesting the in vitro estrogenic activity of bakuchiol. Our data indicated that high doses of bakuchiol (>2 µg/ml) inhibited breast cancer cell growth, with a stronger antiproliferative effect than resveratrol, a widely studied analogue of bakuchiol. High doses of bakuchiol (4 µg/ml, 7 µg/ml and 10 µg/ml) were used for the further in vitro anti-breast cancer studies. Bakuchiol induced ERβ expression and suppressed ERα expression in MCF-7 cells. It also induced S phase arrest in both MCF-7 and MDA-MB-231 cells, which could be rescued by caffeine. Knock-down of p21 also marginally rescued S phase arrest in MCF-7 cells. The S phase arrest was accompanied by the upregulation of ATM, P-Cdc2 (Tyr15), Myt1, P-Wee1 (Ser642), p21 and Cyclin B1, suggesting that blocking of Cdc2 activation may play an important role in bakuchiol-induced S phase arrest. Furthermore, bakuchiol induced cell apoptosis and disturbed mitochondrial membrane potential in MCF-7 cells. The bakuchiol-induced apoptosis was associated with increased expression of Caspase family and Bcl-2 family proteins, suggesting that bakuchiol may induce apoptosis via intrinsic apoptotic pathway. The in vivo anti-breast cancer effect of bakuchiol was further proved in zebrafish (Danio rerio, wild-type AB) xenografts. 0.5 µg/ml of bakuchiol significantly reduced the MCF-7 cell mass in zebrafish xenografts. Overall, these results suggested the potential of using bakuchiol in HRT and breast cancer treatment.